366 views
3 votes
What is the y-intercept of the exponential function? f(x)=−32(2)x−3+3 Enter your answer in the box.

User Muzi Jack
by
5.1k points

2 Answers

4 votes

y-intercept for x = 0.

Substitute x = 0 to the equation of the function:


f(x)=-32(2)^(x-3)+3\\\\f(0)=-32(2)^(0-3)+3=-32(2)^(-3)+3=-32\cdot(1)/(2^3)+3=-32\cdot(1)/(8)+3\\\\=-4+3=-1\\\\Answer:\ \boxed{y-intercept=-1\to(0,\ -1)}

User Jeremy Dunn
by
4.7k points
4 votes

Answer:

-1

Explanation:

We are given that a function


f(x)=-32(2)^(x-3)+3

We have to find the y- intercept of the exponential function.

To find the y- intercept of given exponential we will substitute x=0

Substitute x=0 then, we get


f(0)=-32(2)^(0-3)+3


f(0)=-32(2)^(-3)+3


f(0)=-(32)/((2)^3)+3

By using property
a^(-x)=(1)/(a^x)


f(0)=-(32)/(8)+3


f(0)=-4+3=1

Hence, the y- intercept of given exponential =-1

User Krunal Patil
by
4.4k points